Diversification of university income: Polish practice and international solutions - Andrzej Rozmus; Karolina Cyran (e-Finanse: Financial Internet Quarterly, 2012)
In the face of global economic problems European (and not only European) universities are forced to diversify their income. The constant and stable stream of governmental funds for education is beginning to dry up.For the majority of Polish universities the main and noticeably dominant source of income are the revenues from teaching activity. Thus the current diversification of universities' revenues appears to be just a fiction. The situation is even worse because of both the global economic crisis and the imminent decrease in the birth rate. Polish universities should follow funding models of foreign leaders, who successfully deal with diversification of their revenues. Obviously we cannot compare such universities as Harvard or Oxford with Polish universities, but some of their solutions are worth following. Only by diversifying sources of their revenues will Polish universities be able to compete with the foreign leaders and secure a stable basis for development and use of their potential.
Keywords: I21; I22; I28; 330; higher education; financing higher education; diversification income